Antimicrobial resistance - are future prescribers aware? A study among undergraduate medical students in Kumaon region - Mohd Maroof; Mohd Najmul Aqib Khan; Zafar Masood Ansari; Sadhana Awasthi; Preeti; Rupali Gupta; Kartik Krishan Atri (Asian Journal of Medical Sciences, 2023)
Background: According to the WHO, antimicrobial resistance (AMR) occurs when bacteria, viruses, fungi, and parasites change over time and no longer respond to medicines making infections harder to treat and increasing the risk of disease spread, severe illness, and death and is a global issue and measures to halt this is the need of the hour.